“I really thought nothing could be done”: help-seeking behaviour among women with urinary incontinence - Jürgensen, Martina; Elsner, Susanne; Pedersen, Louise Schreiber; Lückert, Jessica; Faust, Elke; Rudnicki, Martin; Waldmann, Annika (International Journal of Research in Medical Sciences, 2017)
Background: This study explores help-seeking behaviour among women with Urinary Incontinence (UI). Help-seeking behaviour is interpreted as the result of a process which is influenced by several factors, such as the appraisal of symptoms, individual characteristics, experiences within the health-care system, especially with regard to health professionals’ reactions to personal needs, social norms, and information about health issues. Methods: The study was carried out between 2012 and 2014 in Northern Germany and followed an exploratory qualitative study design. Four semi-structured focus group interviews were undertaken with women affected by involuntary loss of urine. 49 women, aged 41 to 86 years old, participated in the focus groups. Thorough sampling of study participants was carried out to warrant demographic and cultural variation and, resultantly, the completeness of perspectives relevant to this field. The verbatim transcripts of the interviews were analyzed following the content analysis method of Mayring. The analysis combined deductive and inductive approaches. Results: Important barriers to seeking medical help were identified: women’s interpretation of UI as a non-medical problem, the lack of knowledge about the causes and treatment of UI, shame and taboo, and the problem of naming “it”. Also, the study results showed factors which supported women’s decision to seek medical help, notably the severity of symptoms or the women’s feeling of losing control of her bodily functions and significant parts of everyday life. Conclusion: The results of the study allow recommendations about measures that can be taken to improve the situation of women affected with UI.